Optimization and Transparency of Village Fund Management: An Islamic Economic Perspective - Wilda Marjana; Cut Dian Fitri; Rina Desiana (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
Optimizing and ensuring transparency in the management of Village Funds is essential for promoting community development and social well-being; however, these efforts are frequently undermined by misuse and corruption. Although Islamic economics offers a robust ethical framework grounded in justice, trust, and public interest, existing studies largely examine village fund management from a general perspective and rarely integrate Islamic economic principles, particularly within the specific context of Aceh Province. This descriptive qualitative study aims to analyze the optimization and transparency of village fund allocation from an Islamic economic perspective in Lampisang Dayah Village, Aceh Besar. Data were collected through direct observation, document analysis, and in-depth interviews with nine village officials and five community members selected using snowball sampling. The findings indicate that village fund management in Lampisang Dayah Village has reached an optimal and transparent level consistent with Islamic economic principles. Optimization is reflected in participatory planning processes that involve the community, including women, as well as in the implementation of pro-welfare programs such as Direct Cash Assistance and food security initiatives that support the public good. Transparency is realized through regular financial reporting to local authorities and the provision of accessible project information boards for the public. Nevertheless, challenges remain in expanding fund capacity for long-term infrastructure development and strengthening women’s active participation. This study contributes theoretically and practically to the discourse on equitable and sustainable village fund management and offers a contextual model that may be replicated in other villages.